Resilience and synergy/trade-off relationship of soil-vegetation system in dump reclamation of surface coal mines on the Loess Plateau - Fu CHEN; Yanfeng ZHU; Zhanbin LUO; Yuanyuan CHANG; Yongjun YANG; Jing MA (Meitan xuebao, 2024)
The interaction and feedback between soil and vegetation will promote the restoration of damaged mine ecosystems towards a virtuous cycle, especially in surface mine dump site reclamation areas. However, the lack of understanding of the correlation and mutual feedback mechanism between vegetation restoration and soil functions limits the scientific formulation of vegetation reconstruction strategies for surface mine dump sites. This study aims to reveal the trade-off and synergistic relationship between vegetation succession and soil system functions during the vegetation restoration process. Using methods such as field surveys, high-throughput sequencing, and resilience assessment models, four reclamation areas with different reclamation timings were selected in the Heidaigou surface coal mine on the Loess Plateau, and a resilience assessment model and trade-off synergy were constructed for five plant restoration types: grassland, shrub, coniferous forest, broad-leaved forest and mixed forest. The results show that: ① compared with bare land, the recovery degree of soil indicators is 30%−80% and the vegetation index recovery degree is 20%−75% after 8−30 a of restoration. ② The recovery rate of soil nutrient conservation and ecological carbon sink functions of grassland and shrubs peaked at 15 a, and the recovery rate of coniferous forest, broadleaf forest and mixed forest peaked at 25 a. The recovery degree of the soil system is mixed forest > grassland > coniferous forest > broadleaf forest > shrubs, and the vegetation system recovery is mixed forest > broadleaf forest > coniferous forest > grassland > shrubs. ③ In terms of the overall trend, the functional resilience of grassland, shrub and broad-leaved forest vegetation and soil systems is mainly in a trade-off relationship, while coniferous forest and mixed forest are mainly in a synergistic relationship. It concludes that the vegetation restoration significantly improves the physical, chemical, biological properties and vegetation community characteristics of the reclaimed soil, the reclamation years significantly affects the recovery elasticity and rate of the soil-vegetation system in the surface mine area of the Loess Plateau, China. As the reclamation years increase, there is a trade-off relationship between soil-vegetation system indicators. The research results confirm that different vegetation types have temporal characteristics in improving the resilience of the soil-vegetation system. Therefore, it is recommended to appropriately adjust the vegetation clustering strategy, allocate vegetation types in a timely manner, and fully coordinate the relationship between various soil functions to optimize the surface mine ecology of the Loess Plateau. The study provides a scientific basis for the restoration planning and management of disturbed surface mine.